Forget colonialism? : sacrifice and the art of memory in Madagascar - Cole, Jennifer, 1966- (Ethnographic studies in subjectivity., 2001)
While doing fieldwork in a village in east Madagascar that had suffered both heavy settler colonialism and a bloody anticolonial rebellion, Jennifer Cole found herself confronted by a puzzle. People in the area had lived through almost a century of intrusive French colonial rule, but they appeared to have forgotten the colonial period in their daily lives.